2009
DOI: 10.1177/1077801209346712
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Victimization and Parenting Stress: Assessing the Mediating Role of Depressive Symptoms

Abstract: Guided by the spillover hypothesis and process model of parenting, this study examined relationships between intimate partner violence (IPV) victimization and parenting characteristics among a sample of 1,153 lower-income women. Hierarchical regression was used to investigate a mediational model examining women's self-reports of physical and psychological IPV, depressive symptoms, and parenting stress. Results suggest that depressive symptoms partially mediate the link between a mother's psychological IPV vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 62 publications
(64 reference statements)
4
54
1
1
Order By: Relevance
“…These findings provide further support for the notion that maternal IPV may exert its influence on parenting directly (Casanueva et al 2008;Levendosky et al 2006). In contrast to the current study, some previous studies have shown that associations between IPV and parenting were mediated by maternal mental health (Levendosky and Graham-Bermann 2001;Levendosky et al 2003;Renner 2009). …”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…These findings provide further support for the notion that maternal IPV may exert its influence on parenting directly (Casanueva et al 2008;Levendosky et al 2006). In contrast to the current study, some previous studies have shown that associations between IPV and parenting were mediated by maternal mental health (Levendosky and Graham-Bermann 2001;Levendosky et al 2003;Renner 2009). …”
Section: Discussioncontrasting
confidence: 79%
“…A large body of research has revealed the negative impacts of depression on parenting (Goodman examined the role of depression in explaining associations between IPV and parenting. In a sample of low-income women, Renner (2009) found that depression partially mediated the relationship between mothers' psychological IPV and self-reported parenting stress. Findings suggested that depression accounts for why psychological IPV renders these mothers less able to handle their parenting demands.…”
Section: Ipv Depression and Parentingmentioning
confidence: 97%
See 2 more Smart Citations
“…Cabe destacar que, mesmo quando não foi encontrada uma correlação positiva entre a violência conjugal e os problemas de comportamento da criança (Zerk et al, 2009) Em relação às habilidades maternas, a maioria dos estudos analisados demonstrou impactos negativos da exposição à violência conjugal, com um aumento do estresse parental das mães (Renner, 2009) e de comportamentos agressivos por parte da mãe (Damant et al, 2010;Taylor et al, 2009;Kelleher et al, 2008), sendo que Letourneau, Fedick e Willms (2007) demonstraram que mães de crianças expostas à violência doméstica podem, de fato, compensar a exposição à violência dos filhos nas suas interações maternas, dando indicativos de que algumas mulheres conseguem superar sua experiência de vitimização e oferecer maternagem adequada aos filhos. Cabe destacar, contudo, que, dentre os estudos que verificaram os impactos da violência conjugal nas habilidades maternas, apenas alguns utilizaram gruposcontrole (Duggan et al, 2009;Jouriles et al, 2009 …”
Section: Considerações Finaisunclassified